Aplikasi THE MODEL Untuk Level Organisasi - Arief Fahmie; Nopriadi Hermani; Muthia Nurrakhmi (Universitas Islam Indonesia, 2015)
An organization needs to determine its development model that is able facilitate it to achieve the goals of development and for improving both the individuals and performances. The MODEL is a personal development design-based on Islamic ideology that combines artificial intelligence theories and Islamic concepts. It consists of four components The Principle (Islam Principle and Sunnatullah Principle), The Vision (True Vision and Big Vision), The Character (Islamic Personality and Efective Character), and The Responsibility (Personal Responsibility and Mabdai Responsibility). This paper aims to describe a theoretical application of The MODEL in organizational context. Applications of it in organizations are related to key elements that exist in the organization: the people, the work, the formal organization, and the informal organization. The MODEL for organizations is also applied in accordance with organization life cycle. The applications connected with key elements of organization and organization life cycle focus not only on personal development, but also have responsibility to build a world civilization based on Islamic rules (syariah).